PENGARUH PERMAINAN PAPAN MENCOCOKKAN ANGKA TERHADAP KEMAMPUAN PENGENALAN BILANGAN ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA KAYUAGUNG - Emelia, Reza; Ilhami, Akmillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low ability to recognize number concepts in children aged 4–5 years. The purpose of this study was to determine the effect of the number matching board game on children's number recognition abilities. The study used a quantitative approach with a quasi-experimental method (pre-experimental) through a one group pretest–posttest design. The research sample consisted of 16 children in group A at Kindergarten Negeri Pembina Kayuagung who were selected using a saturated sampling technique. Data were collected through structured observation using checklist sheets, smartboards, and LKPD arranged based on number recognition indicators. Data analysis included validity and reliability tests, Chi-Square normality tests, and hypothesis tests using t-tests. The results of the normality test showed that the data were normally distributed (x² count ≤ x² table). The hypothesis test showed that tcount (3.53) ≥ ttable (1.75) so that H₀ was rejected and H₁ was accepted. These results prove that the number matching board game has an effect on children's number recognition abilities. Game-based learning media has been proven effective in stimulating the cognitive development of early childhood, especially in the aspect of early numeracy.